A before and after cross-sectional analysis of a public health campaign to increase kidney health awareness in a Canadian province. (December 2015) - Ryz, Krista; Tangri, Navdeep; Verrelli, Mauro; Schneider, Jan; Lesyk, Amie; Eng, Amanda; Hiebert, Brett; Whitlock, Reid; Sood, Manish; Rigatto, Claudio; Komenda, Paul
Abstract Background Chronic kidney disease (CKD) has a major impact on patient health and health system resources. The prevalence of kidney disease is increasing, with Manitoba being one of the provinces in Canada with the highest per capita rate of CKD and end stage renal disease (Anonymous, Canadian organ replacement register annual report: treatment of end-stage organ failure in Canada, 2001–2010, 2011). In 2011, a public health campaign to promote kidney health, by increasing awareness of CKD and its risk factors, was created to target high-risk individuals such as First Nations and those with hypertension and diabetes in urban and rural/remote Manitoba. In this study, we aimed to determine the effectiveness of this public health campaign on increasing the awareness of CKD. Methods Our public health campaign ran in March 2011, and employed a multifaceted approach with radio, television, internet, and print advertisements. Campaign awareness and understanding of the public health message were assessed with a telephone omnibus survey of randomly selected individuals with a Manitoba area code during February and April 2011. A before and after cross-sectional analysis was utilized to measure the effect of exposure to the campaign in telephone respondents. Results 1606 individuals participated in the survey (804 pre and 802 post). Overall awareness of the campaign messaging increased from 7 % pre campaign to 25 % in the post campaign period. Approximately two-thirds of respondents correctly identified a main theme message of the campaign. Awareness improved across most subgroups surveyed aside from those with lower education and income. Conclusions Our study demonstrates the effective reach of our campaign and its relative effectiveness at raising awareness of chronic kidney disease and its risk factors.